2021
DOI: 10.3389/fpls.2021.746464
|View full text |Cite
|
Sign up to set email alerts
|

High Leaf Respiration Rates May Limit the Success of White Spruce Saplings Growing in the Kampfzone at the Arctic Treeline

Abstract: Arctic Treeline is the transition from the boreal forest to the treeless tundra and may be determined by growing season temperatures. The physiological mechanisms involved in determining the relationship between the physical and biological environment and the location of treeline are not fully understood. In Northern Alaska, we studied the relationship between temperature and leaf respiration in 36 white spruce (Picea glauca) trees, sampling both the upper and lower canopy, to test two research hypotheses. The… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 64 publications
2
12
2
Order By: Relevance
“…The much higher rates of respiration at the northern range limit of this species support our first research hypothesis and may help explain not only why white spruce is not found further to the north, but also why the boreal forest biome transitions to tundra at these high northern latitudes (Griffin et al, 2021). Plants acclimated to cold temperatures often have higher rates of respiration measured at a common temperature and a steeper respiratory temperature response (Atkin & Tjoelker, 2003; Körner, 1989; Reich & Oleksyn, 2004) as a means to maintain metabolic function in cold environments.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…The much higher rates of respiration at the northern range limit of this species support our first research hypothesis and may help explain not only why white spruce is not found further to the north, but also why the boreal forest biome transitions to tundra at these high northern latitudes (Griffin et al, 2021). Plants acclimated to cold temperatures often have higher rates of respiration measured at a common temperature and a steeper respiratory temperature response (Atkin & Tjoelker, 2003; Körner, 1989; Reich & Oleksyn, 2004) as a means to maintain metabolic function in cold environments.…”
Section: Discussionsupporting
confidence: 71%
“…Second, while our previous study did not find canopy position differences in respiration at the northern FTE site (Griffin et al, 2021), we hypothesize that at our southern site, upper canopy leaves will have higher respiration rates and be less responsive to temperature than lower canopy leaves. Third, while our previous study found very high respiration rates at the FTE (Griffin et al, 2021), we hypothesize that southern white spruce respiration will be similar to the average for the Needle‐leaved Evergreen (NLEv) plant functional type (PFT) to which they belong. To quantify white spruce respiratory temperature response and make these comparisons, we use two models, the global polynomial model of Heskel et al (2016) and the thermodynamic model of Liang et al (2018).…”
Section: Introductioncontrasting
confidence: 62%
See 2 more Smart Citations
“…2021). Griffin et al (2021) posit that this high respiratory cost may constrain the northern limit of white spruce and the Arctic treeline in general. With the addition of photosynthetic traits measured on the same trees, we are now in a unique position to examine the degree to which this respiratory cost is matched by photosynthetic carbon gains and whether a lower carbon balance may contribute to the northern limits of white spruce’s latitudinal range.…”
Section: Introductionmentioning
confidence: 99%